Customer service for hospitality and tourism - Hudson, Simon (Goodfellow Publishers, 2013)
Provides the 'whys' and 'hows'of customer service. Easy to read, very current, and full of references to all the latest research. Chapters cover financial and behavioural consequences of customer service, consumer trends, developing and maintaining a service culture, managing service encounters, CRM and much more.